Examining the Effectiveness of an Integrated Mindfulness and Self-Care Technique Protocol on the Psychological Well-Being of Parents with Developmentally Delayed Children (Single-Case Study) - Etemadan, Maryam; Samani, Siamak; Amini Manesh, Sajjad; Bardideh, Mohammad Reza (KMAN Counseling & Psychology Nexus, 2024)
The presence of developmentally delayed children in a family leads to disruptions in the psychological well-being of the parents. This study aimed to examine the effectiveness of an integrated protocol combining mindfulness techniques and self-care on the psychological health of parents with developmentally delayed children. The research method used in this study was an experimental single-case design with an ABA model. The statistical population consisted of all parents of children aged 2 to 5 years who were screened for developmental delays by pediatric specialists in the city of Bushehr. Mothers filled out the ASQ3 questionnaire, and the children were referred to a psychologist specializing in child disorders and rehabilitation in the second half of 2022 at two psychological clinics. From this population, 5 couples (10 parents) were selected based on inclusion and exclusion criteria through random sampling. The interventions were implemented for the couples in 16 sessions. The research tool used was the Goldberg and Hillier General Health Questionnaire (1979). Data analysis was performed at two levels: intra-session and inter-session. The findings of the study indicated that the integrated intervention of mindfulness and self-care techniques significantly improved the psychological well-being and mental health of parents with developmentally delayed children. Based on the study’s findings, the effectiveness of the integrated mindfulness and self-care interventions on the psychological well-being of parents with developmentally delayed children was confirmed. Therefore, this intervention can be considered as a valuable and practical treatment for parents of these children.